Improving Students' Mathematics Learning Outcomes through the Problem Based Learning Model at MI Mathla'ul Anwar Rejo Agung - Heniyati; Muslimah (MANDAILING GLOBAL EDUKASIA, 2024)
The problem in this study is the low mathematics learning outcomes of class III students of MI Mathla'ul Anwar Rejoagung Katibung South Lampung. This study aims to improve student learning outcomes in mathematics learning for class III students of MI Mathla'ul Anwar Rejoagung Katibung South Lampung in the 2021/2022 academic year through the PBL Model. The classroom action research method is carried out in 2 cycles. Each cycle consists of planning, implementation, observation and reflection. The results of the study show that using the PBL model in Mathematics learning can improve the Mathematics learning outcomes of class III students of MI Mathla'ul Anwar Rejoagung Katibung South Lampung in the 2021/2022 academic year. This can be seen from the increase in learning outcomes in the first cycle with a passing percentage of 67.35% increasing in the second cycle to 89.36%. Based on these results, it can be concluded that the problem based learning model can be used as an alternative in order to overcome the problem of low student learning outcomes in mathematics learning in elementary schools.